Electronic commerce: formation of contract under Malaysian law / by Loo Chun Boon - Loo, Chun Boon (2003)
The subject of contract formation is a fundamental component of the law of contract as all aspects of contractual performance are dependent on a contract being properly formed. The purpose of this Thesis is to examine how the novelties introduced by the Internet and other electronic media like Electronic Data Interchange (EDI) and electronic mails affect the existing legal principles concerning formation of contracts under the law of Malaysia. This Thesis argues that the existing law in Malaysia governing the formation of contracts is fraught with uncertainty when applied to the Internet and other electronic media. This Thesis submits that these lacunae in the law adversely affect the growth of electronic commerce in Malaysia and Parliament must take the initiative to speedily enact new statutory provisions to address the shortcomings identified in order to introduce more certainty into the law for the benefit of the business and legal communities. This Thesis deals with the interaction of the electronic media with five aspects of contract formation, namely, the contractual capacity of sophisticated computers (in Chapter 2), the doctrine of offer and acceptance (in Chapter 3), the contractual incapacity of minors and persons of unsound mind (in Chapter 4 ), the requirement of writing for the purpose of contract formation (in Chapter 5) and the requirement of signature for the purpose of contract formation (also in Chapter 5). In addition to the foregoing , this Thesis argues against the abandonment of the existing proper law doctrine for ascertaining the law governing the formation of Internet based contracts, and asserts that lawyers and academics have sometimes exaggerated the difficulties of ascertaining (.J ~., ~~ .I ::' <C the governing law of an Internet based contract (in Chapter 6). For comparative purposes, this Thesis examines the statutes and other regulatory directives introduced in a number of Commonwealth nations and also nations with advanced electronic commerce economy (namely, Singapore, the United States, Hong Kong, the European Union and Australia) dealing with electronic commerce generally, and electronic contracts specifically (in Chapter 7). In addition to being the concluding chapter, Chapter 8 of this Thesis also discusses if electronic contracts and electronic commerce generally should best be regulated by statutory intervention, case law development or selfregulation. Throughout this Thesis, a lot of attention is directed to the provisions found under the UNCITRAL Model Law of Electronic Commerce 1996, a copy whereof is reproduced in the Appendix of this Thesis for ease of reference. Although the UNCITRAL Model Law is an excellent precedent of provisions concerning electronic contracts and electronic commerce, this Thesis cautions against rigidly replicating these model provisions without fully comprehending the unique requirements of Malaysia. The law as contained in this Thesis is that as of August 2003 .